Respuestas

2013-04-28T00:38:50+02:00

Evaluamos en el polinomio G(x)=3x^2-1 ;

 

para x=1G(1) = 3. 1^2-1= 2;

 

parax=-1 igual que en el anterior;

 

para x=2G(2)=3.2^2-1=11;

 

para x=-3G(-3)=3.(-3)^2-1=26

  • Usuario de Brainly
2013-04-28T01:08:20+02:00

P(x) = 3x² - 1

 

entonces para

x = 1 → P(1) = 3.(1)² - 1 → P(1) = 3 - 1→P(1) = 2

 

x = - 1→ P( - 1) = 3.(- 1)² - 1→ P(- 1) = 3 - 1→P(-1) = 2

 

x = 2 →  P(2) = 3.(2)² - 1→P(2) = 12 - 1→ P(2) = 11

 

x = - 3→ P(- 3) = 3.(- 3)² - 1→ P(- 3) = 27 - 1→ P(- 3) = 26

 

espero que te sirva, salu2!!!!